Pollination biology of yellow passion fruit (Passiflora edulis forma flavicarpa) at typical Indonesian small-scale farming - RAMADHANI EKA PUTRA; GUNAWAN WIBISANA; IDA KINASIH; RIKA RAFFIUDIN; RC HIDAYAT SOESILOHADI; HERY PURNOBASUKI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Putra RE, Wibisana G, Kinasih I, Raffiudin R, Soesilohadi RCH, Purnobasuki H. 2023. Pollination biology of yellow passion fruit (Passiflora edulis forma flavicarpa) at typical Indonesian small-scale farming. Biodiversitas 24: 2179-2188. Yellow passion fruit (Passiflora edulis forma flavicarpa) has been considered one of the potential local fruits targeted as the export commodity of Indonesia. However, this fruit production level is relatively unstable, which lowers their potency as cash crops and makes them secondary fruits for small-scale farmers. One of the possible factors related to this condition is pollination success. This research aimed to study the pollination biology of yellow passion fruit in terms of flower interaction with insects and the morphological aspect of flowers. The observation was conducted in four sites at Kampung Organik Beji, Wonogiri Regency, between January-February 2022. Pollinators' census was done by scan sampling while flower-visiting insect activities were monitored by focal sampling. This study found 26 species of flower-visiting insects which can be grouped into 5 Ordo and 12 Families with moderate diversity index (H’=2.15), evenly distributed (J’=0.66), and low domination (D=0.32). Among identified insects, carpenter bees (Xylocopa latipes), stingless bees (Tetragonula laeviceps), and Asiatic honey bees (Apis cerana) were considered as pollinators in which X. latipes (Vt=11.81±7.44 second, Fvr=2.41±1.55) visited flower (Vt) on shorter times, and more flower visitation rate (Fvr) than T. laeviceps (Vt=12.36±8.32 second, Fvr=1.10±0.30). Furthermore, this study found that the benefit of natural pollination was better than hand cross-pollination. However, the benefit was hampered by a lack of plant protection and soil fertility management. This study may be applied as baseline information to create pollinator protection zones in the area near the plantation zone to ensure the pollination services for crops.